The functions of nonsuicidal self-injury: converging evidence for a two-factor structure. Issue 1 (December 2015) - Klonsky, E.; Glenn, Catherine; Styer, Denise; Olino, Thomas; Washburn, Jason
Abstract Research has identified more than a dozen functions of non-suicidal self-injury (NSI), but the conceptual and empirical overlap among these functions remains unclear. The present study examined the structure of NSI functions in two large samples of patients receiving acute-care treatment for NSI. Two different measures of NSI functions were utilized to maximize generalizability of findings: one sample (n = 946) was administered the Inventory of Statements About Self-injury (ISAS; Klonsky and Glenn in J Psychopathol Behav Assess 31:215–219, 2009), and a second sample (n = 211) was administered the Functional Assessment of Self-Mutilation (FASM; Lloyd et al. in Self-mutilation in a community sample of adolescents: descriptive characteristics and provisional prevalence rates. Poster session at the annual meeting of the Society for Behavioral Medicine, New Orleans, LA, 1997). Exploratory factor analyses revealed that both measures exhibited a robust two-factor structure: one factor represented Intrapersonal functions, such as affect regulation and anti-dissociation, and a second factor represented Social functions, such as interpersonal influence and peer bonding. In support of the two-factor structure's construct validity, the factors exhibited a pattern of correlations with indicators of NSI severity that was consistent with past research and theory. Findings have important implications for theory, research, and treatment. In particular, the two-factor framework should guide clinical assessment, as well as future research on the implications of NSI functions for course, prognosis, treatment, and suicide risk.